2016
DOI: 10.1016/j.msec.2015.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nb on the β → α″ martensitic phase transformation and properties of the newly designed Ti–Fe–Nb alloys

Abstract: A series of Ti-7Fe-xNb (x=0, 1, 4, 6, 9, 11 wt.%) alloys was designed and cast to investigate the β→α″ martensitic phase transformation, β phase stability, the resulting microstructure and mechanical properties. Phase analysis revealed that only Ti-7Fe-11Nb alloy shows a single body-centred cubic β phase microstructure while the others are comprised of β and orthorhombic α″ phases. Moreover, Nb addition up to 11 wt.% enhances the stability and volume fraction of β phase in the microstructure, hence reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 150 publications
(54 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…However, it has been reported that the use of Ti–6Al–4V alloy as an implant would harm people's health by releasing Al and V elements. Furthermore, high Young's modulus and brittle deformation behavior, caused by the α ′ phase formed inside the struts of the porous sample, may have an adverse effect in longer‐term medical applications . To remove the above disadvantages, low‐modulus β ‐type titanium alloys containing non‐toxic elements may be used as alternative implant materials.…”
Section: Ebm‐produced Titanium Alloysmentioning
confidence: 99%
“…However, it has been reported that the use of Ti–6Al–4V alloy as an implant would harm people's health by releasing Al and V elements. Furthermore, high Young's modulus and brittle deformation behavior, caused by the α ′ phase formed inside the struts of the porous sample, may have an adverse effect in longer‐term medical applications . To remove the above disadvantages, low‐modulus β ‐type titanium alloys containing non‐toxic elements may be used as alternative implant materials.…”
Section: Ebm‐produced Titanium Alloysmentioning
confidence: 99%
“…Basically, pure Ti has a hexagonal close‐packed (hcp) structure at room temperature, called α phase . A phase transformation from hcp structure to body‐centered cubic (bcc) structure would take place for pure Ti at 883 °C (allotropic temperature), namely β phase . Many previous investigations show that the phase transformation temperature of pure Ti can be strongly influenced by alloying elements .…”
Section: Alloy Development and Mechanical Behaviormentioning
confidence: 99%
“…[4,14,33]. In order to test these effects, tensile properties (i.e., UTS: ultimate tensile strength, YS: yield strength, RA: reduction in area, and EL: elongation) for VT3-1 alloy in various states were evaluated.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Meanwhile, the strength of IA samples increases with increasing drawing deformation. Because the retained β phase is dispersed at triple points of α phase and α phase bears a large fraction of total deformation [2,4], the similar volume fraction of equiaxed α grains (~80%) for IA samples is chosen to assess the mechanical properties. The Hall-Petch equation has been described for several classes of two-phase alloys [34,35]:…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation